1986
DOI: 10.1126/science.3715461
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Factors of Breast Cancer Cells Partially Replace Estrogen to Promote Tumor Growth

Abstract: The hormone 17 beta-estradiol acts through its receptor system to induce MCF-7 human breast cancer cells to form tumors in athymic mice. In vitro studies have identified the production of estrogen-induced growth factors from MCF-7 cells that may have a role in growth control. These induced growth factors were sufficient to stimulate MCF-7 tumor growth in ovariectomized athymic mice, thus partially replacing estradiol. Growth factors may act as estrogen-induced "second messengers" in estrogen-responsive growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(71 citation statements)
references
References 9 publications
4
64
1
2
Order By: Relevance
“…Transforming growth factors (TGF alpha, TGF beta) are able to cause reversible phenotypic transformation of fibroblasts (Hsuan, 1989). In hormone dependent MCF-7 breast cancer cells, oestrogen-induced growth factors were identified that may have a role in growth control and might act as oestrogen-induced 'second messengers' in oestrogen-responsive growth of human breast cancer (Dickson et al, 1986;Knabbe et al, 1987). Our statistical analysis revealed an interdependence between the oestrogen receptor status of breast carcinomas and the ecto-5'-NT-expression of the adjacent stromal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factors (TGF alpha, TGF beta) are able to cause reversible phenotypic transformation of fibroblasts (Hsuan, 1989). In hormone dependent MCF-7 breast cancer cells, oestrogen-induced growth factors were identified that may have a role in growth control and might act as oestrogen-induced 'second messengers' in oestrogen-responsive growth of human breast cancer (Dickson et al, 1986;Knabbe et al, 1987). Our statistical analysis revealed an interdependence between the oestrogen receptor status of breast carcinomas and the ecto-5'-NT-expression of the adjacent stromal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of an autocrine FGF growth loop would then free the cells from stromal control during tumor progression. Supporting this hypothesis is the ®nding that certain ER-negative breast tumor-derived cell lines express some of the FGFs (Dickson et al, 1986;Ethier, 1995); and MCF-7 cells transfected with a cDNA encoding FGF-4 formed tumors in ovariectomized mice (McLesky et al, 1993). These latter data contrast with our ®ndings, but it should be noted that the major di erence found by these authors between FGF-4-expressing MCF-7 and parental MCF-7 cells is the ability of the FGFexpressing cells to form tumors in vivo, where the angiogenic ability of FGFs could play a role.…”
Section: Mcf-7 T47dmentioning
confidence: 99%
“…Estrogen acts by activating the estrogen receptor (ER), a member of the nuclear receptor superfamily that dimerizes upon ligand binding, and regulates transcription from ERE (estrogen response element)-containing promoters in a cell-type speci®c manner (Tsai and O'Malley, 1994). The mechanism by which estrogen acts as a mitogen is still unclear; the consensus until recently was that its mitogenic e ect is partially mediated by the induction of growth factor signaling pathways (Dickson et al, 1986). Recent data however indicate that estrogen action may directly modulate the activity of cell cycle regulatory genes and cause phosphorylation of Rb (Altucci et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…TGFα relates structurally to epidermal growth factor (EGF) [7] and binds to epidermal growth factor receptor (EGFR) on the cell surface [8]. Since the expression of TGFα is reported to be modulated by estrogen [9][10][11][12][13][14] and it is well established that ovariectomy (OVX) induces a marked involution of the mammary gland, we addressed the question whether the change in the TGFα level has a role in the mammary gland involution after OVX.…”
Section: Animals and Treatmentsmentioning
confidence: 99%